2020
DOI: 10.1186/s41240-020-00157-8
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inclusion effect of yacon, ginger, and blueberry on growth, body composition, and disease resistance of juvenile black rockfish (Sebastes schlegeli) against Vibrio anguillarum

Abstract: Background: To minimize the use of antibiotics and to obtain a more sustainable fish culture and aquaculture industry, development of alternative natural source of immunostimulant to replace antibiotic in aquafeed is highly needed. Objective: Dietary inclusion effect of yacon (YC), ginger (GG), and blueberry (BB) on growth, body composition, and disease resistance of black rockfish against Vibrio anguillarum was compared to ethoxyquin (EQ). Methods: Four hundred eighty juvenile (an initial weight of 4.2 g) fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…tarda infection. Lee et al (2020) also found that a diet supplemented with 1% YC achieved higher survival of rockfish than a diet with 0.01% ethoxyquin against V . anguillarum .…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…tarda infection. Lee et al (2020) also found that a diet supplemented with 1% YC achieved higher survival of rockfish than a diet with 0.01% ethoxyquin against V . anguillarum .…”
Section: Discussionmentioning
confidence: 95%
“…Lee et al (2021) found that the incorporation of various plant‐derived additives in the diet had no effect on the whole body composition of rockfish. Unlike these studies, however, a variety of phyto‐ingredients were found to alter the whole body composition of rockfish (Kim et al, 2016; Kim et al, 2018; Lee et al, 2020; Lee, Yun, et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations